2001
DOI: 10.1002/pen.10759
|View full text |Cite
|
Sign up to set email alerts
|

Reactive blending of poly (dimethylsiloxane) with nylon 6 and poly (styrene):Effect of reactivity on morphology

Abstract: Reactive compatibilization was used to control and stabilize 20-30 wt% poly(dimethylsiloxane) (PDMS) dispersions in nylon 6 (PA6) and poly(styrene) (PS), respectively. The effect of the type of reaction (amine (NH,)/anhydride (An), NH,/ epoxy (E) and carboxylic acid (COOH)/E) on the morphology was studied with electron microscopy. PS and PDMS have mutual solvents and thus it was possible to use gel permeation chromatography (GPC) to determine the concentration of block copolymer in PS/PDMS blends. Reactive ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Jorzik and Wolf [16] focused also on the reduction of the interfacial tension between PDMS and polyethylene oxide (PEO) affected by the molecular architecture and chemical composition of the compatibiliser. This was consistent with Macosko et al [7,17], who proved that the copolymer compatibiliser needed to be short enough to diffuse quickly to the interface, but also long enough to prevent coalescence during the mixing of the blend. In the frame of our work, the influence of the different natures of polysiloxane on the final morphology of EVA/ polysiloxane reactive blends was evaluated.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Jorzik and Wolf [16] focused also on the reduction of the interfacial tension between PDMS and polyethylene oxide (PEO) affected by the molecular architecture and chemical composition of the compatibiliser. This was consistent with Macosko et al [7,17], who proved that the copolymer compatibiliser needed to be short enough to diffuse quickly to the interface, but also long enough to prevent coalescence during the mixing of the blend. In the frame of our work, the influence of the different natures of polysiloxane on the final morphology of EVA/ polysiloxane reactive blends was evaluated.…”
Section: Introductionsupporting
confidence: 87%
“…Furthermore, a few studies have demonstrated the reactive blending of PDMS with organic polymers. Macosko et al [7] worked on the reactive compatibilisation of PDMS with polyamide 6 (PA6) and polystyrene (PS), involving PDMS with modified epoxy or anhydride end-groups. Zhou and Osby [9] also demonstrated the formation of polycarbonate (PC)/ PDMS compatibilised blends through the use of hydroxylterminated PDMS (PDMS-OH).…”
Section: Introductionmentioning
confidence: 99%
“…η r approaching unity should theoretically result in the minimum domain sizes . Previous studies demonstrated that the amine‐maleic anhydride coupling with similar chain lengths achieved a sub‐micron domain size in other blend systems, even with relatively low η r (η r < 0.05) . Even using completely functional terpolymer, without dilution with non‐functional copolymer, and having η r close to unity, we were not able to achieve sub‐micron dispersions.…”
Section: Resultsmentioning
confidence: 65%
“…The molecular weights were measured relative to linear PMMA standards. Prior to analysis, polymer samples containing PAS were quenched with phenyl isocyanate to prevent sticking of the amine groups onto the column …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation